Potential modeling and performance analysis of junction-less quadruple gate MOSFETs for analog and RF applications. (August 2017) - Rawat, Akash Singh; Gupta, Santosh Kumar
Abstract: In this paper, a quasi-3-D analytical model for Junction-less quadruple MOSFET is presented. The model is developed based on an equivalent number of gates by solving two 2-D Poisson's equations instead of solving complex full 3-D Poisson's equation considering it as two double gate MOSFETs. The model is verified for different channel length, height (or width), oxide thickness, doping concentration, and bias voltages. The presented device is then analysed for digital, analog and RF performance parameters using numerical computations. It has been shown in the paper that the JLQG provides improved gain and SCEs with increase of channel length and decrease in height (or width), oxide thickness and doping concentration whereas a higher cut-off frequency is obtained by decreasing channel length and increase in height (or width), oxide thickness and doping concentration. The doping affects the device performance parameters the most.